Dietary Enteromorpha Polysaccharides Supplementation Improves Breast Muscle Yield and Is Associated With Modification of mRNA Transcriptome in Broiler Chickens - Zhao, Yue; Balasubramanian, Balamuralikrishnan; Guo, Yan; Qiu, Sheng-Jian; Jha, Rajesh; Liu, Wen-Chao (Frontiers in Veterinary Science, 2021)
The present study evaluated the effects of dietary supplementation of Enteromorpha polysaccharides (EP) on carcass traits of broilers and potential molecular mechanisms associated with it. This study used RNA-Sequencing (RNA-Seq) to detect modification in mRNA transcriptome and the cognate biological pathways affecting the carcass traits. A total of 396 one-day-old male broilers (Arbor Acres) were randomly assigned to one of six dietary treatments containing EP at 0 (CON), 1000 (EP_1000), 2500 (EP_2500), 4000 (EP_4000), 5500 (EP_5500), and 7000 (EP_7000) mg/kg levels for a 35-d feeding trial with 6 replicates/treatment. At the end of the feeding trial, six birds (one bird from each replicate cage) were randomly selected from each treatment and slaughtered for carcass traits analysis. The results showed that the dietary supplementation of EP_7000 improved the breast muscle yield (p < 0.05). Subsequently, six breast muscle samples from CON and EP_7000 groups (three samples from each group) were randomly selected for RNA-Seq analysis. Based on the RNA-Seq results, a total of 154 differentially expressed genes (DEGs) were identified (p < 0.05). Among the DEGs, 112 genes were significantly upregulated, whereas 42 genes were significantly down-regulated by EP_7000 supplementation. Gene Ontology enrichment analysis showed that the DEGs were mainly enriched in immune-related signaling pathways, macromolecule biosynthetic, DNA-templated, RNA biosynthetic, and metabolic process (p < 0.05). Kyoto Encyclopedia of Genes and Genomes pathway analysis showed that the DEGs were enriched in signaling pathways related to viral infectious diseases and cell adhesion molecules (p < 0.05). In conclusion, dietary inclusion of EP_7000 improves the breast muscle yield, which may be involved in improving the immunity and the cell differentiation of broilers, thus promoting the muscle growth of broilers. These findings could help understand the molecular mechanisms that enhance breast muscle yield by dietary supplementation of EP in broilers.